Confederate States of America records - Confederate States of America; Wadsworth, James Wolcott, 1846-1926.; Confederate States of America. Department of Justice; Confederate States of America. Department of State; Confederate States of America. Department of the Treasury; Confederate States of America. Navy.; Confederate States of America. Post-Office Department; Confederate States of America. War Department
Correspondence, proclamations, messages of the president, court cases, minute books, docket books, customs records, financial papers, letterbooks, orders, reports, accounts, receipts, and other records relating to the formulation of the government of the Confederacy and the conduct of its internal, external, and military affairs. Includes records of the departments of state, justice, treasury, navy, war and post office along with material related to the president, congress, and constitution.
Records of the Department of State have been traditionally known as the Pickett Papers and include correspondence of secretary of state J. P. Benjamin with diplomats in Belgium, France, Great Britain, and Mexico, the James Wolcott Wadsworth collection of related material, and other records.
Correspondents include Bolling Baker, G. T. Beauregard, J. P. Benjamin, C. C. Clay, Lewis Conger, Jefferson Davis, Edwin DeLeon, Anthony J. Guirot, Charles J. Helm, Lewis Heyliger, Henry Hotze, L. C. Q. Lamar, A. Dudley Mann, J. M. Mason, C. G. Memminger, John T. Pickett, John A. Quintero, John H. Reagan, Raphael Semmes, John Slidell, Alexander Hamilton Stephens, Jacob Thompson, William Henry Trescott, LeRoy Pope Walker, and William Lowndes Yancey.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Microfilm of originals in private hands.
Private
Library of Congress Prints and Photographs Division.
Collection material in English.
Keywords: Baker, Bolling -- Correspondence; Beauregard, G. T. -- 1818-1893 -- Correspondence; Benjamin, J. P. -- 1811-1884 -- Correspondence; Clay, C. C. -- 1816-1882 -- Correspondence; Conger, Lewis -- Correspondence; Davis, Jefferson, -- 1808-1889.; Davis, Jefferson, -- 1808-1889 -- Correspondence; DeLeon, Edwin, -- 1828-1891 -- Correspondence; Guirot, Anthony J. -- Correspondence; Helm, Charles J. -- Correspondence; Heyliger, Lewis -- Correspondence; Hotze, Henry, -- 1833-1887 -- Correspondence; Lamar, L. Q. C. -- 1825-1893 -- Correspondence; Mann, A. Dudley -- 1801-1889 -- Correspondence; Mason, J. M. -- 1798-1871 -- Correspondence; Memminger, C. G. -- 1803-1888 -- Correspondence; Pickett, John T. -- 1822-1884 -- Correspondence; Quintero, John A. -- Correspondence; Reagan, John H. -- 1818-1905 -- Correspondence; Semmes, Raphael, -- 1809-1877 -- Correspondence; Slidell, John, -- 1793-1871 -- Correspondence; Stephens, Alexander Hamilton, -- 1812-1883 -- Correspondence; Thompson, Jacob, -- 1810-1885 -- Correspondence; Trescott, William Henry, -- 1822- -- Correspondence; Walker, Leroy Pope, -- 1817-1884 -- Correspondence; Yancey, William Lowndes, -- 1814-1863 -- Correspondence; Confederate States of America; Confederate States of America. -- Army. -- Army of Tennessee -- Surgeons; Confederate States of America. -- Congress; Confederate States of America; Diplomatic and consular service, Confederate; Executive departments -- Confederate States of America; Legislative bodies -- Confederate States of America; Belgium -- Foreign relations -- Confederate States of America; Confederate States of America -- Foreign relations -- Belgium; Confederate States of America -- Foreign relations -- France; Confederate States of America -- Foreign relations -- Great Britain; Confederate States of America -- Foreign relations -- Mexico; Confederate States of America -- Armed forces; Confederate States of America -- Officials and employees; Confederate States of America -- Politics and government; France -- Foreign relations -- Confederate States of America; Great Britain -- Foreign relations -- Confederate States of America; Mexico -- Foreign relations -- Confederate States of America; United States -- History -- Civil War, 1861-1865.